2015
DOI: 10.1159/000371856
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Survival after Pancreatoduodenectomy for Ductal Adenocarcinoma Depend on Patients' Age

Abstract: Background: It is supposed that a prolonged lifetime will be associated with increased incidence of PDAC among the elderly. Some studies show a tendency toward decreased survival in the elderly patients following pancreatoduodenectomy for PDAC. The aim of this study was to evaluate factors, influencing survival following pancreatoduodenectomy for PDAC in different age groups. Methods: Data of 251 patients after pancreatoduodenectomy for PDAC between 1999 and 2012 were analyzed. The Kaplan-Meier method and log-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…There are several tumor-related prognostic factors for PDAC, including tumor differentiation, vascular invasion, perineural invasion, lymph node metastasis, and systemic spread. Among these, the tumor grade appears to be one of the most important predictors of survival [6, 7]. It is agreed that pathological confirmation is not required in an operable pancreatic tumor; consequently, the latter variable remains unknown prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are several tumor-related prognostic factors for PDAC, including tumor differentiation, vascular invasion, perineural invasion, lymph node metastasis, and systemic spread. Among these, the tumor grade appears to be one of the most important predictors of survival [6, 7]. It is agreed that pathological confirmation is not required in an operable pancreatic tumor; consequently, the latter variable remains unknown prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 21 studies were identified (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). A total of 6,933 PDs were collected, and of these, 1,931 PDs (27.9%) were performed in elderly patients.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The current study presents a median survival rate of 109.1 months, corresponding to the data from other high volume centres [9,13] . Five-year (58.4%) and 10-year (39.5%) actuarial survival rates indicate carcinoma of ampulla of Vater having probably one of the best overall survival rates among periampullary carcinomas, especially as compared to the carcinoma of the head of the pancreas [14,15] . This can be attributed to earlier presentation because of the anatomic location of the tumour, and by the difference in biological aggressiveness compared with pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%